Religious Authority as Human Life Guidelines - Ati Ati (UIN Sunan Gunung Djati Bandung, 2018)
This article was conducted to discuss the fading of the response of some people to religion. This response grew in line with emerge of various social phenomena of disappointment. Faith is also considered by some people to no longer be able to support the problem of life. Religion is deemed to be irrelevant to the demands of modernity. God and Religion in the perspective of some societies are then different from the views of the community in general. The authority of the life guidance held by humans is that religion is often only understood as a system of belief or belief in the teachings of God, which has implications for the understanding that religion is a theological doctrine. It is due to the cult of